2014
DOI: 10.1021/nn406119j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Relationship between Support Porosity and the Stability of Pore-Confined Metal Nanoparticles Studied on CuZnO/SiO2 Methanol Synthesis Catalysts

Abstract: Metal nanoparticle growth represents a major deactivation mechanism of supported catalysts and other functional nanomaterials, particularly those based on low melting-point metals. Here we investigate the impact of the support porous structure on the stability of CuZnO/SiO2 model methanol synthesis catalysts. A series of silica materials with ordered cagelike (SBA-16 mesostructure) and disordered (SiO2-gel) porosities and varying pore sizes were employed as catalyst supports. Nitric oxide moderated nitrate dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 65 publications
2
57
0
1
Order By: Relevance
“…catalysts was stable during the methanol synthesis at similar conditions [23]. During synthesis of these catalysts, co-impregnation of copper and zinc led to the incorporation of zinc in the silica support, resulting in a zinc-silicate, which is more stable than ZnO and SiO 2 separately [60].…”
Section: Catalytic Performancementioning
confidence: 92%
See 1 more Smart Citation
“…catalysts was stable during the methanol synthesis at similar conditions [23]. During synthesis of these catalysts, co-impregnation of copper and zinc led to the incorporation of zinc in the silica support, resulting in a zinc-silicate, which is more stable than ZnO and SiO 2 separately [60].…”
Section: Catalytic Performancementioning
confidence: 92%
“…Irrespective of the mechanism, particle growth is generally considered to depend on the reaction conditions [14], the metal-support interaction [15][16][17], the particle size (distribution) [18,19] and the interparticle spacing [20][21][22], and also on the geometry of the support [9,15,16,23,24]. It has for instance been shown that particle migration can be restricted by encagement or entrapment [23][24][25][26][27]. The geometry of the support can also affect the thermodynamic stability of a supported nanoparticle since the chemical potential of a supported nanoparticle depends on the contribution of the metal-support interfacial energy [3,28].…”
Section: Introductionmentioning
confidence: 99%
“…The CuO sintering process is correlated with this alteration. In fact this effect is closely related to the metal loading and the textural properties of the support [60,61].…”
Section: Characterization Of the Cu/sba-r-500 Adsorbent After 7 Operamentioning
confidence: 99%
“…Although the micropores are blocked and no longer accessible, the mesopores are still reachable. The existence of copper oxide particles inside the mesopores is advantageous for the copper oxide dispersion, since pore confinement will prevent further metal oxide particle growth within the pores [31]. Finally, when comparing the average pore size of the materials, a significant increase can be recognized for the ADP sample.…”
Section: Textural Propertiesmentioning
confidence: 99%